Cervical Cancer in the Baltic States: Can Intelligent and Personalised Cancer Screening Change the Situation? - Stankūnas, Mindaugas; Pärna, Kersti; Tisler, Anna; Ķīvīte-Urtāne, Anda; Kojalo, Una; Zodzika, Jana; Baltzer, Nicholas; Nygard, Jan; Nygard, Mari; Uuskula, Anneli (Acta medica Lituanica, 2022)
The three Baltic States (Estonia, Latvia, and Lithuania) are among the European Union countries with the highest incidence and mortality rates for cervical cancer. In order to tackle this public health challenge, there is an urgent need to implement more advanced and effective methods in cervical cancer prevention in Baltic countries.Nationwide cervical cancer screening programs in the Baltic States commenced in 2004–2009. While the organized screening programs in these countries differ in some relevant details (target age groups, screening interval), the underlying principles and problems, barriers are universal. However, the outcomes of present screening programs are unsatisfactory. In addition, universal screening programs are extremely costly. There is a potential need for more intelligent and personalized cervical cancer screening program. In 2019 the project “Towards elimination of cervical cancer: intelligent and personalized solutions for cancer screening” (2020–2023) was developed with the main objective – to develop improved and personalized cancer screening methods within a sustainable health care system.It is expected, that more sophisticated cervical cancer screening model will be implemented in Estonia, Latvia, and Lithuania, and will have a positive impact to epidemiology of cervical cancer and public health in general.
Keywords: Cervical cancer; prevention; screening; Estonia; Latvia; Lithuania